Rapid Growth Cone Uptake and Dynein‐Mediated Axonal Retrograde Transport of Negatively Charged Nanoparticles in Neurons Is Dependent on Size and Cell Type. Issue 2 (22nd November 2018) - Lesniak, Anna; Kilinc, Devrim; Blasiak, Agata; Galea, George; Simpson, Jeremy C.; Lee, Gil U.
Abstract: Nanoparticles (NPs) are now used in numerous technologies and serve as carriers for several new classes of therapeutics. Studies of the distribution of NPs in vivo demonstrate that they can be transported through biological barriers and are concentrated in specific tissues. Here, transport behavior, and final destination of polystyrene NPs are reported in primary mouse cortical neurons and SH‐SY5Y cells, cultured in two‐compartmental microfluidic devices. In both cell types, negative polystyrene NPs (PS(−)) smaller than 100 nm are taken up by the axons, undergo axonal retrograde transport, and accumulate in the somata. Examination of NP transport reveals different transport mechanisms depending on the cell type, particle charge, and particle internalization by the lysosomes. In cortical neurons, PS(−) inside lysosomes and 40 nm positive polystyrene NPs undergo slow axonal transport, whereas PS(−) outside lysosomes undergo fast axonal transport. Inhibition of dynein in cortical neurons decreases the transport velocity and cause a dose‐dependent reduction in the number of accumulated PS(−), suggesting that the fast axonal transport is dynein mediated. These results show that the axonal retrograde transport of NPs depends on the endosomal pathway taken and establishes a means for screening nanoparticle‐based therapeutics for diseases that involve neurons. Abstract : The transport behavior and final destination of polystyrene nanoparticles are reported in the axons and somata of primary cortical neurons and SH‐SY5Y cells. These results show that the axonal retrograde transport of nanoparticles depends on the endosomal pathway taken and establishes a means for screening nanoparticle‐based therapeutics for diseases that involve neurons.